IMPLEMENTATION OF MARRIAGE ISBAT IN SYAMTALIRA BAYU DISTRICT, NORTH ACEH REGENCY: ANALYSIS OF OBSTACLES AND EFFORTS TO IMPROVE ACCESS TO PUBLIC SERVICES - Rozatul Jannah; Cut Sukmawati; Sufi; Nur Hafni; Muslem (RADJA PUBLIKA, 2025)
This study focuses on analyzing the implementation of the marriage confirmation program in Syamtalira Bayu District, North Aceh Regency. The main problems identified are related to financial resource constraints and the lack of effective communication between program implementers and the community in the success of the program. The main theory used is the public policy implementation theory of George C. Edward III, which emphasizes the importance of resources, communication, cooperation, and implementer disposition in the sustainability and success of a policy. This research methodology uses a qualitative approach with data collection techniques through in-depth interviews, observations, and document studies with relevant sources, such as the Sharia Court, the Islamic Sharia Office, and the District Office of Religious Affairs (KUA). The results show that the success of the marriage confirmation program is greatly influenced by the availability of stable and transparent funds from the government, the positive disposition of implementing officers, and effective communication between agencies. In addition, good resource management and cross-institutional collaboration are key supporting factors.